2012
DOI: 10.1021/jp211791r
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Rotational Structure in the High-Resolution Infrared Spectrum of trans-Hexatriene-1-13C1: A Semiexperimental Equilibrium Structure for the C6 Backbone of trans-Hexatriene

Abstract: trans-Hexatriene-1-(13)C(1) (tHTE-1-(13)C(1)) has been synthesized, and its high-resolution (0.0015 cm(-1)) infrared spectrum has been recorded. The rotational structure in the C-type bands for ν(26) at 1011 cm(-1) and ν(30) at 894 cm(-1) has been analyzed. To the 1458 ground state combination differences from these bands, ground state rotational constants were fitted to a Watson-type Hamiltonian to give A(0) = 0.8728202(9), B(0) = 0.0435868(4), and C(0) = 0.0415314(2) cm(-1). Upper state rotational constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Bands of the trans -1- d 1 species in the spectrum were too badly overlapped to be analyzable. A third investigation was for tHTE-1- 13 C 1 . Not only were ground state rotational constants obtained for this species, but strong evidence was supplied to show that the ground state rotational constants for the 2- 13 C 1 and 3- 13 C 1 species could be predicted accurately from computed values.…”
Section: Ground State and Equilibrium Rotational Constants For Trans-...mentioning
confidence: 99%
See 2 more Smart Citations
“…Bands of the trans -1- d 1 species in the spectrum were too badly overlapped to be analyzable. A third investigation was for tHTE-1- 13 C 1 . Not only were ground state rotational constants obtained for this species, but strong evidence was supplied to show that the ground state rotational constants for the 2- 13 C 1 and 3- 13 C 1 species could be predicted accurately from computed values.…”
Section: Ground State and Equilibrium Rotational Constants For Trans-...mentioning
confidence: 99%
“…Scale factors for A 0 , B 0 , and C 0 were found as the obsd/calcd ratios for the normal species. These scale factors were then applied to the calculated ground state rotational constants for the 2- 13 C 1 and 3- 13 C 1 species to obtain the predictions . The last investigation was the analysis of rotational structure in bands of tHTE-2- d 1 and -3- d 1 …”
Section: Ground State and Equilibrium Rotational Constants For Trans-...mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 7, this band has a broad central Q branch, reflecting much hot band activity. The comparable bands in the spectra of tHTE [5] and tHTE-1-13 C1 [7] near 1010 cm -1 were hard to analyze. The band in the spectrum of tHTE-2-d was more difficult.…”
Section: 26 the Fourth Band Of Thte-2-d To Be Investigated Was The mentioning
confidence: 99%
“…Previously, high-resolution IR spectroscopy yielded rotational constants for transhexatriene [5], the 1,1-d2 species [6], the cis-1-d1 species [6], and the 1-13 C1 species [7]. As part of the work on the 1-13 C1 species, it was shown that the rotational constants for the 2-13 C1 and 3-13 C1 species could be predicted from quantum chemical (QC) calculations with good accuracy [7]. Remaining to be found are the ground state (GS) rotational constants for the 2-d1 and 3-d1 species.…”
mentioning
confidence: 99%